Chitosan/nanocellulose-based bionanocomposite films for controlled betamethasone and silver sulfadiazine delivery - Riccio, Bruno Vincenzo Fiod [UNESP]; Klosowski, Ana Beatriz; Prestes, Eduardo; de Sousa, Taynara Barbosa; de Assunção Morais, Laís Caroline; Lemes, Bruna Mikulis; Beltrame, Flávio Luís; Campos, Patrícia Mazureki; Ferrari, Priscileila Colerato (Wiley, 2021)
Bionanocomposite films based on chitosan and nanocellulose (nanocrystals or nanofibrils) have gained considerable attention for biomedical applications, especially for wound dressings. However, the development of these films as controlled drug release dressings is still under-exploited. Therefore, this work aimed to design chitosan/nanocellulose-based bionanocomposite films, loaded by betamethasone or silver sulfadiazine, as functional dressings. The films were obtained by solvent casting and characterized by physicochemical, mechanical, barrier properties, in vitro drug release, and antimicrobial activity. The nanocellulose type, physical state, and content caused influence on the film's properties providing different physical, barrier, and drug release profiles. They are semi-occlusive and mechanically resistant; the drug release is controlled, and possesses antimicrobial activity. In conclusion, the developed biodegradable bionanocomposite films are promising as active dressings for controlled drug delivery in the wound site and have specific applications according to their features to treat inflamed and purulent wounds, non-infectious dry wounds, and infectious wounds.
Keywords: biodegradable; biomedical applications; drug delivery systems